Autoimmunity to polymorphonuclears: functional consequences of the binding of antibodies to membrane and cytoplasmic target antigens of polymorphonuclear leukocytes - Bartůnková, J; Araujo, A; Hrusák, O; Sedivá, A (Journal of clinical immunology, 1997)
Antineutrophil autoantibodies reacting with cytoplasmic antigens are associated with various types of vasculitides, whereas antibodies reacting with neutrophil membrane antigens are mostly related to autoimmune neutropenias. The aim of this study was the investigation of the effect of monoclonal antibodies (MoAbs) reacting with surface and cytoplasmic antigens of polymorphonuclear leukocytes (PMN) known to be targets for autoantibodies in human diseases. Blood of healthy volunteers was tested for several phagocytic functions in the presence of MoAbs against surface (CD16, CD11b, CD18, NB1) and cytoplasmic (proteinase 3; PR3) molecules. Candidacidal activity was significantly inhibited in the presence of all MoAbs but isotypic control. Phagocytic activity was inhibited by anti-CD11b and/or anti-CD18 MoAbs. Zymosan-induced chemiluminescence was reduced by MoAbs anti-CD16, CD18, and NB1, enhanced by anti-PR3 MoAb, and less enhanced by anti-CD11b. In conclusion, antimembrane antibodies diminished phagocytic functions at multiple steps; in contrast, anticytoplasmic MoAb promoted activation of oxidative burst in addition to impairment of microbicidal activity. This fact may be related to different pathogenic aspects of diseases associated with antimembrane and anticytoplasmic antibodies.
Keywords: antigeny povrchové; Candida albicans; CD18 Antigens; luminiscenční měření; makrofágový antigen 1; Autoimmunity; vazba proteinů; Antibodies, Monoclonal; lidé; receptory IgG; Humans; Macrophage-1 Antigen; Autoantibodies; Antigen-Antibody Reactions; Neutrophils; fagocytóza; autoantigeny; Phagocytosis; neutrofily; Receptors, IgG; reakce antigenu s protilátkou; autoimunita; Cytoplasm; monoklonální protilátky; antigeny CD18; Antigens, Surface; Autoantigens; Protein Binding; cytoplazma; Luminescent Measurements; autoprotilátky